Implementation of the Think-Pair-Share Cooperative Model to Improve Reading Comprehension Skills of Fifth Grade Students at MIN 25 Pidie - Irmayani; Adriana (MANDAILING GLOBAL EDUKASIA, 2025)
This Classroom Action Research (CAR) was initiated to address the persistent challenge of low reading comprehension skills among Fifth Grade students at MIN 25 Pidie, a factor critical for academic success. The study sought to investigate the effectiveness of the Think-Pair-Share (TPS) cooperative learning model as an intervention strategy. The research subjects comprised 28 students from the class, and the study was implemented across two iterative cycles, following the standard CAR procedure of planning, action, observation, and reflection. Data collection utilized observation sheets to assess student activity and validated reading comprehension tests to measure learning outcomes. The findings revealed a substantial and significant improvement in student performance. The mean score for reading comprehension ability dramatically increased from a baseline mean of 58.75 in the pre-test to a mean of 72.50 in Cycle I, and subsequently reached 85.36 in Cycle II. Crucially, the percentage of students meeting the Minimum Completeness Criterion (MCC) also rose markedly, culminating in 89.28% attainment in Cycle II. This level surpassed the performance indicator set for the research. The research concludes that the application of the Think-Pair-Share cooperative learning model is highly effective in significantly enhancing the reading comprehension skills of Fifth Grade students at MIN 25 Pidie. The model successfully fostered active engagement, facilitated collaborative discussion, and promoted deeper processing of textual information. The study recommends the TPS model be integrated into routine instructional planning to improve overall literacy outcomes.